Fluid gels: a new feedstock for high viscosity jetting - Holland, Sonia; Tuck, Christopher; Foster, Tim (Springer, 2018)
Suspensions of gel particles which are pourable or spoonable at room temperature can be created by shearing a gelling biopolymer through its gelation (thermal or ion mediated) rather than allowing quiescent cooling – thus the term ‘fluid gel’ may be used to describe the resulting material. As agar gelation is thermoreversible this type of fluid gel is able to be heated again to melt agar gel particles to varying degrees then re-form a network quiescently upon cooling, whose strength depends on the temperature of re-heating, determining the amount of agar solubilised and subsequently able to partake in re-gelation. Using this principle, for the first time fluid gels have been applied to a high viscosity 3D printing process wherein the printing temperature (at the nozzle) is controllable. This allows the use of ambient temperature feedstocks and by altering the nozzle temperature, the internal nature (presence or absence of gel particles) and gel strength of printed droplets differs. If the nozzle prints at different temperatures for each layer a structure with modulated texture could be created.